The additive effect of dorzolamide hydrochloride (Trusopt) and a morning dose of bimatoprost (Lumigan) on intraocular pressure and retrobulbar blood flow in patients with primary open-angle glaucoma. Issue 10 (16th June 2010) - Stankiewicz, Andrzej; Wierzbowska, Joanna; Siemiątkowska, Anna; Fuksińska, Beata; Robaszkiewicz, Jacek; Zegadło, Arkadiusz; Ehrlich, Rita; Siesky, Brent; Harris, Alon
Abstract : Aims: To assess the additive effect of dorzolamide hydrochloride 2% on the diurnal intraocular pressure (IOP) curve and retrobulbar haemodynamics in patients with primary open-angle glaucoma (POAG) treated with morning-dosed bimatoprost 0.03%. Methods: Twenty-five patients with POAG were evaluated in a prospective, single-masked study. After a 1 week run-in period with bimatoprost all patients were treated with bimatoprost dosed once in the morning for 1 month, after which dorzolamide was added twice daily for 2 months. Goldmann applanation IOP, arterial blood pressure (ABP) and heart rate were measured every 2 h for 24 h and diurnal ocular perfusion pressure (OPP) was calculated. Colour Doppler imaging (CDI) of the ophthalmic artery (OA) and the central retinal artery (CRA) was recorded five times daily. All measurements were taken after the two phases of treatment and were compared. Results: The mean baseline IOP was 14.8±3.5 mm Hg. Mean IOP following bimatoprost monotherapy (12.8±2.9 mm Hg) and after 2 months of dorzolamide adjunctive therapy (12.2±2.6 mm Hg) were not statistically significantly different (p=0.544). Only at the 4:00 h time point was IOP significantly reduced using the bimatoprost/dorzolamide combined treatment (p=0.013). The 24 h IOP fluctuations were lower when dorzolamide was added (6.0±2.3 mm Hg vs 4.6±1.5 mm Hg, p=0.0016). Repeated analysis of variance detected a significant decrease of vascular resistance in the OA (p=0.0167) with adjunctive dorzolamide treatment. Conclusions: The addition of dorzolamide to morning-dosed bimatoprost had an additive hypotensive effect only on the night-time IOP curve at 4:00 h and resulted in a lower IOP fluctuation. Dorzolamide added to bimatoprost may reduce vascular resistance in the OA.